Bilateral training improves agility and accuracy for both preferred and non-preferred legs in young soccer players - Ben Kahla, A.; Elghoul, Y.; Ammar, A.; Masmoudi, L.; Trabelsi, K.; Glenn, J. M.; Dahmen, R. (Perceptual and Motor Skills, 2022)
As laterality of the lower limbs is regarded as a relevant influence on soccer performance, we assessed whether a bilateral training program for both the preferred leg (PL) and non-preferred leg (NPL) would improve soccer players` lateral asymmetry, agility, and accuracy. Sixty right-foot-dominant young soccer players were randomly assigned to either an experimental group (EXP) that underwent bilateral training or a control group (CONT) that performed their usual training schedule without bilateral exercise. We assessed the players` lateral asymmetries before and after training on four soccer skill tasks: a zigzag test with and without a ball, a receiving and direct volley-shooting accuracy test, and a passing accuracy test. Results showed post-test versus pre-test performance improvements for the EXP group on the index of technical skills and agility (p < .001). A post-hoc analysis further revealed a pre-test to post-test performance improvement on shooting and passing accuracy with both legs only for the EXP group (p < .001). These results support the role of bilateral practice in improving lateral asymmetries, agility, and accuracy.